2022
DOI: 10.1038/s41598-022-07336-8
|View full text |Cite
|
Sign up to set email alerts
|

B-cell-depletion reverses dysbiosis of the microbiome in multiple sclerosis patients

Abstract: To elucidate cross-sectional patterns and longitudinal changes of oral and stool microbiota in multiple sclerosis (MS) patients and the effect of B-cell depletion. We conducted an observational, longitudinal clinical cohort study analysing four timepoints over 12 months in 36 MS patients, of whom 22 initiated B-cell depleting therapy with ocrelizumab and a healthy control group. For microbiota analysis of the oral cavity and the gut, provided stool and oral swab samples underwent 16S rDNA sequencing and subseq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…calcoaceticus both increased (induced proinflammatory responses), but Parabacteroides distasonis was reduced (stimulated anti-inflammatory IL-10-expressing) [99]. In addition, the abundance of Bacteroidetes, Lachnospiraceae, Rikenellaceae, Eisenbergiella, Escherichia-Shigella, F. prausnitzii, and Flavobacterium increased in patients with MS, whereas Firmicutes, Ruminococcaceae, Bacteroides, Bifidobacterium, Clostridium, L. salivarius, L. iners, L. ruminis, Megamonas, Odoribacter, Parabacteroides, and Prevotella decreased [99,[114][115][116][117][118][119][120][121][122][123][124][125][126][127][128] (Fig. 4).…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…calcoaceticus both increased (induced proinflammatory responses), but Parabacteroides distasonis was reduced (stimulated anti-inflammatory IL-10-expressing) [99]. In addition, the abundance of Bacteroidetes, Lachnospiraceae, Rikenellaceae, Eisenbergiella, Escherichia-Shigella, F. prausnitzii, and Flavobacterium increased in patients with MS, whereas Firmicutes, Ruminococcaceae, Bacteroides, Bifidobacterium, Clostridium, L. salivarius, L. iners, L. ruminis, Megamonas, Odoribacter, Parabacteroides, and Prevotella decreased [99,[114][115][116][117][118][119][120][121][122][123][124][125][126][127][128] (Fig. 4).…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…7 A). To validate this model, we used an independent German cohort 23 . We inferred the microbiota-derived metabolites of the 38 HVs and the 12 treatment-free RRMS patients.…”
Section: Resultsmentioning
confidence: 99%
“…Dysbiosis of the oral microbiome in MS patients has been previously described. In a longitudinal study of oral swabs 23 , there were significant increases in the relative abundance of Campylobacter, Haemophilus and Neisseria . In a second study 24 , DNA sequencing of cultured bacterial isolates from oral swabs by PCR revealed that Staphylococcus, Actinomyces, Fusobacterium, Bacteroides, Porphyromonas, Prevotella, Veillonella and Propionibacterium were significantly more abundant in the MS group than in the control group, while Lactobacillus and Peptostreptococcus were more prevalent in the HV group.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Figure 3 illustrates the potential role of gut dysbiosis in MS, although the directionality of this interaction is not clear. Gut microbes are definitely altered in MS patients, and this alteration is associated with the varied severity of the disease ( 125 128 ). The microbiome signature in MS patients is characterized by the lower abundance of F. prausnitzii , Prevotella , and Bacteroides , and a higher abundance of Akkermansia muciniphila ( 126 , 128 ).…”
Section: Microbial Dysbiosis Drives Systemic Autoimmune Diseasesmentioning
confidence: 99%